Associations between teacher training and measures of physical literacy among Canadian 8- to 12-year-old students - Law, Barbi; Bruner, Brenda; Scharoun Benson, Sara M; Anderson, Kristal; Gregg, Melanie; Hall, Nathan; Lane, Kirstin; MacDonald, Dany J; Saunders, Travis J; Sheehan, Dwayne; Stone, Michelle R; Woodruff, Sarah J; et al. (Université d'Ottawa | University of Ottawa, 2018)
Abstract Background Quality physical education (PE) contributes to the development of physical literacy among children, yet little is known about how teacher training relates to this development. We assessed the association between teacher training, and the likelihood that children met recommended achievement levels for components of physical literacy as defined by the Canadian Assessment of Physical Literacy (CAPL). Methods Canadian children (n = 4189; M = 10.72 years, SD = 1.19) from six provinces completed the CAPL. Logistic regression was used to examine the relationship between teacher training (generalist/PE specialist), adjusting for children’s age and gender, and physical competence protocols (sit and reach, handgrip, plank, Progressive Aerobic Cardiovascular Endurance Run [PACER], body mass index [BMI], waist circumference, Canadian Agility and Movement Skill Assessment [CAMSA]), the four CAPL domain scores, and the total CAPL score. Results Teacher training, in addition to children’s age and gender, explained only a very small proportion of variance in each model (all R2 < 0.03). Children taught by a generalist were less likely to reach recommended levels of motivation and confidence (OR = 0.83, 95% CI, 0.72–0.95) or CAMSA scores (OR = 0.77, 95% CI, 0.67–0.90), even when accounting for a significant increase in CAMSA score with age (OR = 1.18, 95% CI, 1.12–1.26). All other associations between measures of components of physical literacy and teacher training were not significant. Conclusions While teacher training is hypothesized to contribute to the development of physical literacy among elementary school students, the observed effects in this study were either small or null. Children taught by PE specialists were more likely than those taught by generalists to demonstrate recommended levels of motivation and confidence, and to have better movement skills, which are hypothesized to be critical prerequisites for the development of a healthy lifestyle. Further research with more robust designs is merited to understand the impact of teachers’ training on the various components of physical literacy development.